Nur Fadhilah Efektivitas Pendekatan STEM Berbasis PBL (Problem Based Learning) Berbantuan Assemblr Edu Terhadap Keterampilan Berpikir Kreatif dan Hasil Belajar Siswa - Nur Fadhilah; Ruqoyyah Nasution; Zenia Lutfi Kurniawati; Nelda Anasthasia Serena (PendIPA Journal of Science Education, 2026)
This study aims to determine the effectiveness of a Problem-Based Learning (PBL)-based STEM approach using Assemblr Edu media on students’ creative thinking skills and learning outcomes in the respiratory system curriculum. This study employed a quantitative method with a quasi-experimental design in the form of a nonequivalent control group design. The study sample consisted of class XI-3 as the experimental group and class XI-4 as the control group at State Senior High School 5 Samarinda. Data collection techniques included achievement tests, observations of creative thinking skills, interviews, and documentation. The research instruments comprised pretest and posttest items, as well as an observation sheet for creative thinking skills covering the indicators of fluency, flexibility, originality, and elaboration. Data were analyzed using normality tests, homogeneity tests, N-Gain tests, and hypothesis testing. The results of the study indicate that the implementation of a PBL-based STEM approach supported by Assemblr Edu is effective in improving students’ creative thinking skills and learning outcomes. The improvement in creative thinking skills is evident from the increase in scores on each indicator of student creativity throughout the learning process. Additionally, the learning outcomes of students in the experimental class were higher than those in the control class after the intervention was administered. The use of the Augmented Reality-based Assemblr Edu platform helps students visualize abstract concepts of the respiratory system, making learning more interactive, contextual and meaningful. Thus, a Problem-Based Learning (PBL)-based STEM approach supported by Assemblr Edu can serve as an innovative alternative in biology education to enhance students’ creative thinking skills and learning outcomes.